A prospective observational study to study and correlate the clinical and microbiological profile of bile cultures in patients with symptomatic cholelithiasis - Shankaran, Ramakrishnan; Amarasekara, Chaminda (International Surgery Journal, 2020)
Background: Biliary infection has been reported in a significant proportion of patients developing gallstones. Many studies have found biliary microflora in 20% to 46% patients with a post-operative infection rate of 7% to 20% in those who undergo cholecystectomy for symptomatic gallstone disease. Various antibiotics are also used empirically as prophylaxis against post-operative infection. The study was conducted in order to determine the bacteriology and to test its sensitivity to commonly used antibiotics of aspirated bile samples taken during laparoscopic cholecystectomy, and to correlate it with the clinical profile recorded in patients with symptomatic cholelithiasis. Methods: A total of 266 patients who underwent laparoscopic cholecystectomy were included in the study over a two year period. Intra operatively, bile was aspirated from gall bladder and sent for culture and antibiotic sensitivity testing. Results: 14.66% (39 out of 266) patients had positive growth with Escherichia coli most commonly isolated in 9.77% (26/266) patients, followed by the Klebsiella species in 4.89% (13 out of 266) patients. All the cultures were sensitive to amikacin and meropenem, 97.44% to imipenem, and only 43.39% were sensitive to ampicillin. A statistically significant correlation was observed between a positive bile culture with the duration of symptoms (p=0.01874) and gall bladder thickness (p<0.0001). No correlation was seen between bile culture and history of acute cholecystitis, number or size of calculi. Conclusions: The results of this study can help develop local guidelines and recommendations based on Indian data to ensure the rational use of prophylactic antibiotics in patients with symptomatic cholelithiasis.